2019
DOI: 10.1111/jocd.12869
|View full text |Cite
|
Sign up to set email alerts
|

Co‐existence of Juvenile dermatomyositis and psoriasis vulgaris with fungal infection: A case report and literature review

Abstract: Summary Introduction The incidence rate of psoriasis vulgaris (PSV) coexisting with Juvenile dermatomyositis (JDM) is low. Through our thorough literature search, we found that PSV arising on JDM with superficial fungal infection of facial skin is rarely reported. So, we hereby, report a case of combination of the above three diseases. Meanwhile, we also reviewed the previous literatures aiming at the related basis, clinical manifestation, diagnosis, and treatment of the diseases. Interestingly, of all cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Conversely, several reports have suggested that PV may be associated with myopathy. Tanabe et al reported that PV may induce myopathy with vascular amyloid deposition (22), and Xing et al demonstrated an association between PV and juvenile DM; however, the muscle pathology was not elucidated (23). PV may have also had a certain impact on the muscle pathology in the present case, via an unknown inflammatory pathway; however, the patient demonstrated myositis-like symptoms during the treatment of PV with cyclosporine A.…”
Section: Discussionmentioning
confidence: 64%
“…Conversely, several reports have suggested that PV may be associated with myopathy. Tanabe et al reported that PV may induce myopathy with vascular amyloid deposition (22), and Xing et al demonstrated an association between PV and juvenile DM; however, the muscle pathology was not elucidated (23). PV may have also had a certain impact on the muscle pathology in the present case, via an unknown inflammatory pathway; however, the patient demonstrated myositis-like symptoms during the treatment of PV with cyclosporine A.…”
Section: Discussionmentioning
confidence: 64%
“…Спочатку це було зумовлено чисто діагностичною проблемою: поява на третьому році від початку хвороби численних бляшкопо дібних сріблястих лускатих висипань, локалі зованих на волосистій частині голови, тулубі та кінцівках, які супроводжувалися незначним свербежем, спричинила низку запитань стосов но їхньої оцінки. Річ в тому, що на той час вже було відомо про можливості паралельного перебігу ЮДМ/ЮДМам/ДМ та псоріазу або виникнення при цих захворюваннях псоріазоподібного висипу [6,12,16,30,36] Читайте нас на сайті: http://med expert.com.ua більш пізні наукові повідомлення про подібні випадки [11,23,26,45] наголошують на серйоз ній проблемі швидкої верифікації діагнозу та неминучій потребі міждисциплінарного під ходу у спробі її вирішення. Аналогічна ситуація склалася при диференціації висипу і в нашого хворого: лише тісна співпраця дитячих кардіо ревматологів, дерматологів, імунологів та мор фологів дозволила констатувати у нього співіс нування двох захворювань.…”
unclassified